Investigation of Factors Affecting the Rate of High-Boiling-Point Solvent Removal Using a Rotary Evaporator - Chen, Yinzhe; Wang, Weiding; Zhang, Qian (Synlett, 2024)
Factors that might affect the removal time of high-boiling-point solvents with a rotary evaporator were examined. Considering several essential factors, the optimized conditions for removing a high-boiling-point solvent are suggested. The results and discussion from this work can serve as a reference for current and future organic chemists. Finally, two examples of fast and successful dehydration reactions are given to demonstrate that the rotary evaporator can be used to conduct organic syntheses.
Keywords: high-boiling solvents; dehydration; organic solvents; solvent removal; rotary evaporator